Helskobinding - i litterær og religionshistorisk belysning - Hansen, Inger Vibeke (Religionsvidenskabeligt Tidsskrift, 1987)
The starting point of this article is the problem of the reliability of information in the Icelandic sagas about Norse religion. It seems that there is a possibility of getting indirect information from the texts themselves. What is attempted here is to find a relationship between the religious information about the custom of tying helskór on a dead person before burial (only known from Gísla Saga) and the literary form of skór in the Icelandic sagas in general. Here shoes seem to form part of the well-known scheme of foreshadowing, i.e. they indicate the coming of death and/or violence. This connection to death/violence could be explained by the use in the funeral ritual. Especially the examples in which a person ties his shoes seem to support this theory. If this is the case, it will also be a support to the authenticity of the funeral custom in Gísla Saga.